2022
DOI: 10.1002/dev.22276
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of infants receiving extra motor stimulation, full‐term control infants, and infants born preterm: High‐density EEG analyses of cortical activity in response to visual motion

Abstract: Electroencephalography was used to investigate the effects of extrastimulation and preterm birth on the development of visual motion perception during early infancy. Infants receiving extra motor stimulation in the form of baby swimming, a traditionally raised control group, and preterm born infants were presented with an optic flow pattern simulating forward and reversed self‐motion and unstructured random visual motion before and after they achieved self‐produced locomotion. Extrastimulated infants started c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 117 publications
0
3
0
1
Order By: Relevance
“…One study [ 42 ] used EEG to access visual evoked potentials (VEPs) and measure the functional integrity of the visual pathways from the retina to the visual cortex of the brain addressing infants’ motion perception, which is crucial for a successful navigation through the environments. A greater improvement of motion perception was observed in extra-stimulated infants (i.e., infants that participated in swimming programs) when compared with full-term, traditionally raised peers and preterm infants [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study [ 42 ] used EEG to access visual evoked potentials (VEPs) and measure the functional integrity of the visual pathways from the retina to the visual cortex of the brain addressing infants’ motion perception, which is crucial for a successful navigation through the environments. A greater improvement of motion perception was observed in extra-stimulated infants (i.e., infants that participated in swimming programs) when compared with full-term, traditionally raised peers and preterm infants [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The positive effect on child neurodevelopment reported by Garcia and colleagues in their systematic review [ 17 ] was confirmed for infants younger than 36 months in the present review. Although three studies had already been included in Garcia et al’s review [ 38 , 39 , 48 ], more recent studies confirmed the positive effects of aquatic activities exposure on infants’ development [ 41 , 42 , 43 , 49 ]. Baby swimming programs were associated with improvements in gross, fine, and total motor development [ 39 , 40 , 41 , 43 ] (even when the children are older [ 38 ]); improvement in motion perception [ 42 ]; and a tendency for an improvement in early executive function skills [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secara khusus, tahap merangkak dimulai dengan upaya canggung untuk bergerak maju dengan perut menyentuh tanah serta sebagian besar bayi mencapai tonggak perkembangan merangkak dengan tangan dan lutut sekitar 9 bulan dan mulai berjalan sendirian setelah 12 bulan (Xiong et al, 2017). Pada usia 9-10 bulan adalah bahwa bayi harus sudah merangkak setidaknya selama minimal 9 minggu (Meer, 2022). Saat bayi mulai merangkak, kemampuan mereka untuk menjelajahi lingkungan meningkat secara dramatis (Herbert et al, 2007).…”
Section: Perbedaan Tingkat Kosentrasi Anak Usia 3-4 Tahun Dengan Mele...unclassified